Realities. (Amsterdam : Arti et Amicitiae Amsterdam, 1992)
Marc Mulders ; Christine Koenigs ; Peter Klashorst ; Jurriaan van Hall ; Bart Domburg ; Phil Bloom ; Siert Dallinga ; Gerard Druiven ; Ronald Hooft ; Anya Janssen ; Helma Pantus ; Ernst Voss ; Jan Worst ; Philip Akkerman ; Sandra Derks ; Marliz Frencken ; Hugo Kaagman ; George Korsmit ; Aldert Mantje ; Rob Scholte ; Diana Blok ; Fortuyn/O'Brien ; Edwin Janssen ; Jorgen Leijenaar ; Thom Puckey ; Teun Hock ; Jan Van Tongeren; Henk Ijkelenstam ; Dora Van Der Veen ; Teunn Nijkamp ; Peter Van Poppel ; Lovis Van Poeteren
vol. V : Realities V - Jan Van Tongeren, Henk Ijkelenstam, Dora Van Der Veen, Teunn Nijkamp, Peter Van Poppel, Lovis Van Poeteren, ongepag. : ill., Exhibition in Circulo de Bellas Artes, Madrid, Spain
Realities, Arti et Amicitiae, Amsterdam, 1993
boek